Effects of substrate and mechanical scarification on the germination of Syagrus oleracea (Arecaceae) seeds - Batista, G. S. [UNESP]; Mazzini, R. B. [UNESP]; Gimenes, R. [UNESP]; Pritchard, H. W.; Pivetta, K. F. L. [UNESP] (Ista-int Seed Testing Assoc, 2011)
The slow and uneven germination of Syagrus oleracea seeds represents a problem for its propagation, especially for commercial production. This work aimed to study the effects of substrate and mechanical scarification on the germination of S. oleracea seeds. Germination (% G), emergence rate (ER), leaf area (cm(2)), root length (cm), leaf dry mass (g) and root dry mass (g) were also determined. Non-scarified seeds sown in vermiculite germinated faster and showed higher germination (65%), as well as greater root length (16.55 cm). leaf dry mass (5.07 g) and root dry mass (12.41 g), when compared to the scarified seeds.